Double Movement Fazlur Rahman dalam Penentuan Status Hukum Transfusi Darah: Menimbang Keharaman dan Kedaruratan - Muhith (Jurnal Ilmu Pendidikan dan Sains Islam Interdisipliner, 2026)
This study aims to analyze the legal status of blood transfusion in Islam through Fazlur Rahman’s Double Movement theory. The main problem arises from the tension between the Qur’anic prohibition of blood and the modern medical use of blood transfusion to save human life. This study uses a qualitative library research method with normative, hermeneutical, and maqashid sharia approaches. The first movement examines the Qur’anic prohibition of blood by tracing its historical context, especially its relation to consumption, impurity, and the prevention of harm. The second movement brings the moral values of the Qur’an into modern medical reality by considering necessity, public benefit, and the protection of life. The findings show that blood transfusion cannot be judged as absolutely forbidden or absolutely permissible. Its legal status depends on medical need, urgency, safety, ethical procedure, and the absence of exploitation. Blood transfusion is permissible when it is needed for valid medical reasons, follows medical standards, and does not harm the donor or recipient. It may become obligatory when it is the only way to save a patient’s life. However, it may be forbidden when it is performed without medical necessity, causes greater harm, involves coercion, or leads to exploitation. This study concludes that Fazlur Rahman’s Double Movement provides a contextual and ethical framework for formulating Islamic legal responses to contemporary medical issues.